Complete aortic prosthetic valve dehiscence after modified Bentall-De Bono procedure - Onur Tasar; Arzu Kalayci; Can Yucel Karabay; Cevat Kirma (International Journal of the Cardiovascular Academy, 2018)
A 56-year-old male patient was admitted to our clinic due to persistent fever despite the use of antibiotics for 2 weeks, chest pain, and presyncope. His medical history revealed that the patient underwent modified Bentall-De Bono procedure 2 months ago due to ascending aortic aneurysm and severe aortic insufficiency. Transthoracic apical 5 chamber view showed that mobile vegetation prolapsed into the left ventricular outflow tract during ventricular diastole and that mechanical prosthetic valve was superior to the aortic annulus. Transesophageal echocardiography revealed normal aortic mechanical prosthetic valve function; however, the valve was positioned more superior to the annular plane and a dense vegetation was observed. Moreover, a complete dehiscence of the prosthetic valve was attached to aortic annulus with a single stitch in an area between noncoronary sinus and left coronary sinus. Dense thrombus formation was observed in the perivalvular region. Many cases with prosthetic valve endocarditis and partial dehiscence as its complication have been reported in the literature. However, to the best of our knowledge, there is no reported case of complete dehiscence secondary to infective endocarditis following complete ascending aortic graft and prosthetic aortic valve replacement (modified Bentall-De Bono procedure).